CARBONDIOXIDE EQUILIBRIA AND NUTRIENT AVAILABILITY IN TWO CULTURE PONDS AT NARAKKAL DURING THREE MONSOON AND POSTMONSOON MONTHS, JUNE-SEPTEMBER, 19R4 - Ramamirtham, C P; Mathew, Annie (Indian Journal of Fisheries, 2011)
The nutrient availability did not show a definite pattern and not much correlation was observed between the biological cycle of nutrients and carbondioxide content. The variations of the different hydrological parameters of the ponds as well as their diurnal variations are discussed.